2020
DOI: 10.1021/jacs.0c11708
|View full text |Cite
|
Sign up to set email alerts
|

DNA G-Quadruplex and i-Motif Structure Formation Is Interdependent in Human Cells

Abstract: Guanine and cytosine-rich nucleic acid sequences have the potential to form secondary structures such as G-quadruplexes and i-motifs, respectively. We show that stabilisation of G-quadruplexes using small molecules destabilises the i-motifs, and vice versa, indicating these gene regulatory controllers are interdependent in human cells. This has important implications as these structures are predominately considered as isolated structural targets for therapy, but their interdependency highlights the interplay o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 21 publications
7
72
0
1
Order By: Relevance
“…Occasionally, due to their different formation requirements or the offset position of the respective C-and G-rich sequences, both structures can form simultaneously [163]. In support of mutual exclusivity, a recent study from the Smith group demonstrates that the formation of one structure destabilizes the structure on the complementary strand [164]. Since G4s and i-motifs appear to have distinct roles in transcriptional regulation, it is reasonable that their formation within the same promoter is interdependent.…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, due to their different formation requirements or the offset position of the respective C-and G-rich sequences, both structures can form simultaneously [163]. In support of mutual exclusivity, a recent study from the Smith group demonstrates that the formation of one structure destabilizes the structure on the complementary strand [164]. Since G4s and i-motifs appear to have distinct roles in transcriptional regulation, it is reasonable that their formation within the same promoter is interdependent.…”
Section: Discussionmentioning
confidence: 99%
“…hnRNP E1 binds to i-motifs formed by poly-C tracts, maintains i-motifs, and suppresses G4s in the cell. Recently it has been observed that i-motifs and G4s are mutually exclusive ( King et al, 2020 ). G4s can inhibit DNA replication, but various proteins including helicases, Fen1, and hnRNPs resolve such structures.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is now clear that non-B-DNA structures are powerful determinants of mutagenesis [106]. There are an abundance of non-B-DNA structures [36], but those that are particularly relevant to gene promoter regions are G-quadruplexes [46,47], i-motifs [65,66], cruciforms [69], triplexes [107], and Z-DNA [108], as illustrated in Figure I. These local non-B-DNA structures are often targets of protein binding, including various transcription factors [109][110][111].…”
Section: Box 2 Non-b-dna Structuresmentioning
confidence: 99%